2007
DOI: 10.17796/jcpd.31.2.6q619k3664634250
|View full text |Cite
|
Sign up to set email alerts
|

An Allergic Reaction Following Intramuscular Administration of Ketamine and Midazolam

Abstract: A 6-year-old female in good health presented with no known drug allergies for dental treatment under general anesthesia. Following the preoperative evaluation, the patient received intramuscular premedication consisting of midazolam (1 mg) and Ketamine (60 mg) into the left deltoid muscle. During patient transfer, anesthesia personnel detected a hive developing in proximity to the patient's right ear lobe. The subject was directly placed into the operative chair, and a physical exam revealed urticaria on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Allergic reactions to ketamine have been described in three reports. They are all pediatric cases ranging from rashes to anaphylaxis (8,9,11). The first patient, a 3-year old child, developed an extensive macular rash attributed to the direct pharmacological effect of the drug rather than an allergy (8).…”
Section: Discussionmentioning
confidence: 99%
“…Allergic reactions to ketamine have been described in three reports. They are all pediatric cases ranging from rashes to anaphylaxis (8,9,11). The first patient, a 3-year old child, developed an extensive macular rash attributed to the direct pharmacological effect of the drug rather than an allergy (8).…”
Section: Discussionmentioning
confidence: 99%
“…Intradermal tests revealed an allergic reaction to ketamine. Boynes et al [122] reported an urticarial response in a 6-year-old girl following the intramuscular administration of ketamine and midazolam. Further skin testing confirmed a positive reaction to ketamine.…”
Section: Ketaminementioning
confidence: 99%
“…Immediate hypersensitivity reaction to ketamine is rare, and despite the drug's long history and widespread use, case reports in the literature are scant . Ketamine reaction with an associated rise in serum tryptase has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%